The prevalence and persistence of maternal morbidities after first vs. second birth: A prospective cohort study in Ireland - Francesca Wuytack; Brenda Lynch; Patrick Moran; Anthony P. Fitzgerald; Paul Corcoran; Cecily Begley; Deirdre Daly (PLoS ONE, 2025)
Background This study aimed to assess the prevalence and persistence of key maternal morbidities – urinary incontinence, faecal incontinence, pelvic girdle pain, sexual health problems, depression, and anxiety – after the births of a first and second baby. Its longitudinal design distinguishes it from previous research by examining a range of morbidities over two childbirths and stratifying results based on women’s prior health history. Methods and findings A prospective cohort of 3,047 nulliparous women completed surveys in early pregnancy and at 3, 6, 9, and 12-months postpartum after their first birth. Of these, 254 women who had a second baby and consented to follow-up completed additional surveys at 6-months and/or 12-months postpartum after their second baby’s birth. Prevalence of each morbidity was reported at each time point, 3, 6, 9, 12-months after the first birth; and 6 and/or 12-months after the second birth. Persistence was defined as reporting the morbidity at 6 and/or 12-months after the first birth and again at 6 and/or 12-months after the second birth. Among 91 women reporting urinary incontinence after their first baby’s birth, persistence was 100% (n = 5/5) for those who experienced it in the 12-months prior to their first pregnancy and 39.5% (n = 34/86) for those without (RR 2.53, 95% CI (1.95–3.29)). For pelvic girdle pain (n = 86), persistence was 98.1% (n = 52/53) who experienced it in the 12-months prior to their first pregnancy and 97.0% (n = 32/33) for those without (RR 1.01, 95% CI (0.94–1.09)). Sexual health problems persisted in 100% (n = 76/76) of those who experienced it in the 12-months prior to their first pregnancy versus 89.6% (n = 43/48) without (RR 1.12, 95% CI (1.02–1.23)). Depression persisted in 50% (n = 4/8) of those who experienced it in the 12 months prior to their first pregnancy versus 19.0% (n = 15/79) without (RR 2.63, 95% CI (1.15–6.03)); and anxiety persisted in 100% (n = 1/1) of those who experienced it in the 12-months prior to their first pregnancy versus 13.5% (n = 12/89) without anxiety (RR 7.42, 95% CI (4.38–12.55)). Conclusions These findings underscore the need for early identification and intervention to mitigate long-term health issues, highlighting the importance of targeted pregnancy and postpartum care for women with prior maternal morbidities.